On multiplication modules and their generalization - Al-Hashimi, Basil; Al-Bahraany, Bahar; Al-Hassani, Ohood (Iraqi Journal of Science, 2025)
R. Jain studied multiplication modules and their generalizations. The aim of this paper is to give various properties for these classes of modules. In particular, we study M N and Hom (M. N), where M and N belongs to these classes.